A Scalable Haze‐Free Antireflective Hierarchical Surface with Self‐Cleaning Capability. Issue 27 (28th July 2022) - Oh, Seungtae; Cho, Jin‐Woo; Lee, Jihun; Han, Jeonghoon; Kim, Sun‐Kyung; Nam, Youngsuk
Abstract: The lotus effect indicates that a superhydrophobic, self‐cleaning surface can be obtained by roughening the topography of a hydrophobic surface. However, attaining high transmittance and clarity through a roughened surface remains challenging because of its strong scattering characteristics. Here, a haze‐free, antireflective superhydrophobic surface that consists of hierarchically designed nanoparticles is demonstrated. Close‐packed, deep‐subwavelength‐scale colloidal silica nanoparticles and their upper, chain‐like fumed silica nanoparticles individually fulfill haze‐free broadband antireflection and self‐cleaning functions. These double‐layered hierarchical surfaces are obtained via a scalable spraying process that permits precise control over the coating morphology to attain the desired optical and wetting properties. They provide a "specular" visible transmittance of >97% when double‐side coated and a record‐high self‐cleaning capability with a near‐zero sliding angle. Self‐cleaning experiments on photovoltaic devices verify that the developed surfaces can significantly enhance power conversion efficiencies and aid in retaining pristine device performance in a dusty environment. Abstract : Bumpy morphology of superhydrophobic coatings scatters incident light, thereby lowering transparency. Here, broadband, haze‐free, and antireflective surfaces with self‐cleaning capability is reported. "Hierarchically" designed coatings provide large "specular" transmittance (>97%) in visible and self‐cleaning capability. As a proof‐of‐concept, experiments are conducted on photovoltaic devices in dusty environment and observed a complete recovery of performance with improved (>6%) power conversion efficiency.